Návrh vstupu na zahraniční trh pro vybraný podnik - Polakovičová, Miroslava (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce se zabývá problematikou vypracování návrhu marketingové strategie vybrané společnosti pro vstup na německý mezinárodní trh. Hlavním cílem je úspěšné působení na Drážďanském trhu pořádáním pop-up akce. Použité teoretické poznatky s informacemi získanými z analýzy současného stavu a prostředí naplňují své vedlejší cíle k dosažení hlavního cíle. Realizace navržených příspěvku by proto měla zajistit větší povědomí o značce na zahraničním trhu.

The master’s thesis deals with the matter of developing a marketing strategy proposal for a selected company to enter the German international market. The main goal is successful engagement on the Dresden market by organizing pop-up event. The used theoretical knowledge with the information obtained from the analysis of the current state and environment, fulfill its secondary goals to achieve the main goal. Therefore, implementation of proposed contributions should result in greater brand awareness on the foreign market.
Proposal of Entry into the Foreign Market for the Selected Company
Keywords: Marketing. Mezinárodní marketing. Marketingová strategie. Mezinárodní výzkum. Expanze na zahraniční trh. Pomalá móda.; Marketing. International Marketing. Marketing strategy. International research. Expansion into the foreign market. Slow fashion.